1968
DOI: 10.1007/bf00394506
|View full text |Cite
|
Sign up to set email alerts
|

Homing and ?ortsteue? (attachment to place) in Patella L. (Gastropoda, Prosobranchia)

Abstract: It is known that numerous gastropods show homing ability. Many limpets return to well defined sites. Patella L. acquires a home spot also on the smooth glass surfaces of aquarium. Before leaving, the limpet scrapes its home, particularly the anterior part of the footprint. After each return it makes characteristic movements with its shell.When homing Patella nearly always retraces its outward track, at least in part; sometimes it reaches its home over the shortest route possible.Site and tracks are marked by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

1980
1980
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(18 citation statements)
references
References 86 publications
0
17
0
Order By: Relevance
“…Since pedal mucus contains significant levels of protein, polysaccharide and other organic substances (reviewed by Davies & Hawkins, 1998), chemical cues have been proposed to drive trail-following in cases such as homing (Funke, 1968;Cook, 1969Cook, , 1971Cook, , 1979Cook & Cook, 1975;Chelazzi et al, 1985), conspecific aggregation (Trott, 1978;Trott & Dimock, 1978), mate-searching (Peters, 1964;Chase et al, 1978;Cook, 1985a;Johannesson et al, 2010;Ng et al, 2011) and predation (Cook, 1985a(Cook, , 1989Marin et al, 1999;Clifford et al, 2003;Shaheen et al, 2005). In an early study, Sleeper & Fenical (1977) reported a yellow hydrophobic substance (containing three methyl ketones) released in mucus trails of the sea slug Nauanax inermis following its disturbance.…”
Section: (2) Cues For Trail Specificitymentioning
confidence: 99%
“…Since pedal mucus contains significant levels of protein, polysaccharide and other organic substances (reviewed by Davies & Hawkins, 1998), chemical cues have been proposed to drive trail-following in cases such as homing (Funke, 1968;Cook, 1969Cook, , 1971Cook, , 1979Cook & Cook, 1975;Chelazzi et al, 1985), conspecific aggregation (Trott, 1978;Trott & Dimock, 1978), mate-searching (Peters, 1964;Chase et al, 1978;Cook, 1985a;Johannesson et al, 2010;Ng et al, 2011) and predation (Cook, 1985a(Cook, , 1989Marin et al, 1999;Clifford et al, 2003;Shaheen et al, 2005). In an early study, Sleeper & Fenical (1977) reported a yellow hydrophobic substance (containing three methyl ketones) released in mucus trails of the sea slug Nauanax inermis following its disturbance.…”
Section: (2) Cues For Trail Specificitymentioning
confidence: 99%
“…Trail-following behaviour occurs in terrestrial snails (COOK 1977;CHASE et al 1978) and, together with distant responses to such trails, explains homing to resting places in slugs (GELPERIN 1974;COOK 1979COOK a, 1980. Homing by trail following has also been proved in various aquatic snails (FUNKE 1968;WELLS & BUCKLEY 1972;COOK 1979b, MCFARLANE 1981. However, concerning hibernation in Helix, trail orientation is unlikely because of the long time interval, 4-5 months, between emergence and hibernation, and seems excluded by the results of displacement experiments: snails removed during winter returned to the original hibernating area and not the place where they emerged in spring.…”
Section: Discussionmentioning
confidence: 93%
“…The hibernation hole is a temporary construction (LIND 1968), and no visible contours are left after 4-5 months, contrary to the permanent resting places of slugs and limpets (FUNKE 1968;COOK 1980;COOK et al 1969). It is therefore likely that Helix does not search for the old sites as such, but responds to a number of previously experienced stimuli which together characterize a goal area associated with hibernation.…”
Section: Discussionmentioning
confidence: 99%
“…from predation; Coleman et al, 2004a) or infochemicals via dissolved or surface-bound cues (Hay, 2009). In addition to containing cues about identity (Funke, 1968;Shaheen et al, 2005), which are important for predator-prey relationships or social networks, surface-bound chemical cues such as mucous trails laid by molluscs or stationary mucus to facilitate attachment can contain information on many other aspects of the emitting organism's biology (Davies and Hawkins, 1998;Ng et al, 2013). For molluscs such as limpets, perception of their chemical environment occurs through chemosensory apparatus on their external membranes (Croll, 1983) and via ingestion of biofilms/mucus (Davies and Hawkins, 1998), which themselves contain chemical cues (Croll, 1983).…”
Section: Introductionmentioning
confidence: 99%